Analisis Pengaruh Permodalan dan Evaluasi Kinerja Keuangan Terhadap Hasil Pemeriksaan Kesehatan Koperasi melalui Manajemen Keuangan sebagai Variabel Mediasi - Sulistyawati, Asih; Mutiara, Nisa (Universitas Islam Kadiri, 2026)
An organization such as a cooperative has characteristics that emphasize the participation of the human resources involved. Cooperatives in Kediri Regency have a significant role in the regional economy. The purpose of this study is to analyze and identify the relationship between capital and financial performance evaluation through financial management on the results of cooperative health checks in Kediri Regency. This research method uses a quantitative descriptive approach. The results of the study are Capital and Financial Performance Evaluation simultaneously or jointly influence Financial Management. The results of data processing show a calculated F value of 6.691494 > F table 3.150 or a Prob. value of 0.000579 < 0.05. 2. Capital, Financial Performance Evaluation, and Financial Management simultaneously or jointly influence Cooperative Health Checks. The results of data processing show a calculated F value of 9.532390 > F table 3.153 or a Prob. value of 0.000032 < 0.05.